2023
DOI: 10.1002/naaq.10273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prey Size, Microalgal Density, and Light Intensity on Survival of Pacific Red Snapper Larvae

Abstract: Development of Pacific Red Snapper Lutjanus peru culture has been impeded by low survival in larval culture. We studied the effects of different culture conditions on larval survival in four experiments that examined (1) different‐size prey at first feeding (nauplii of the copepods Parvocalanus crassirostris and Pseudodiaptomus euryhalinus; rotifers Proales similis; and a mix of these three prey types); (2) microalgal density (3 × 105 and 1 × 106 cells/mL); (3) the presence of adult copepods P. crassirostris i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Furthermore, this Additionally, other plankton species detected in the study have also been reported as live prey for several marine aquatic larvae. For example, Pseudodiaptomus euryhalinus had been documented as live prey for the larvae of Pacific red snapper, Lutjanus peru (Amador- Marrero et al 2023). Calanus finmarchicus has a high 265 and omega-3 fatty acids (36.30%), which are higher than found in a commercial live diet such as Artemia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this Additionally, other plankton species detected in the study have also been reported as live prey for several marine aquatic larvae. For example, Pseudodiaptomus euryhalinus had been documented as live prey for the larvae of Pacific red snapper, Lutjanus peru (Amador- Marrero et al 2023). Calanus finmarchicus has a high 265 and omega-3 fatty acids (36.30%), which are higher than found in a commercial live diet such as Artemia sp.…”
Section: Discussionmentioning
confidence: 99%
“…2022; Pacific Red Snapper Lutjanus peru : Amador‐Marrero et al. 2023) or for ornamental purposes (Yellow Tang Zebrasoma flavescens : Callan et al. 2018; Mandarinfish Synchiropus splendidus : Zeng et al.…”
Section: Introductionmentioning
confidence: 99%